Impact of Psychoeducation on Anger Management and Emotional Awareness in Teenagers - Pan, Yinghao; Zhang, Wei (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to evaluate the effectiveness of a psychoeducational intervention on improving anger management and emotional awareness in adolescents. Methods and Materials: The study employed a randomized controlled trial design with a total of 30 adolescents from China, randomly assigned to an experimental group (n = 15) and a control group (n = 15). The intervention consisted of eight 90-minute psychoeducational sessions focusing on emotional literacy, anger regulation strategies, and communication skills. Participants in both groups completed the State-Trait Anger Expression Inventory-2 (STAXI-2) and the Emotional Awareness Questionnaire (EAQ) at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA) with Bonferroni post-hoc tests in SPSS-27. Findings: Results showed that the experimental group demonstrated significant improvements in both anger management and emotional awareness compared to the control group. For anger management, repeated measures ANOVA indicated a significant interaction effect between time and group (F(2,54) = 20.71, p < .001, η² = .44), with post-hoc tests revealing significant increases from pre-test to post-test (p < .001) and sustained at follow-up (p < .001). Similarly, for emotional awareness, a significant time × group interaction was observed (F(2,54) = 22.89, p < .001, η² = .46), with substantial gains from pre-test to post-test (p < .001) and maintained at follow-up (p < .001). No significant changes were found in the control group across the three assessments. Conclusion: The findings suggest that psychoeducation is an effective and sustainable intervention for enhancing anger regulation and emotional awareness among teenagers. The program not only produced immediate benefits but also maintained improvements over a five-month period, highlighting its potential as a preventive emotional health strategy in adolescence.